Evaluasi Usability dan Perbaikan Antarmuka Pengguna pada Website Malang Night Paradise menggunakan Metode Human Centered Design (HCD) - Satrio Vianka Manaman; Hanifah Muslimah Az-Zahra; Herman Tolle (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Malang Night Paradise is a tourist attraction and family entertainment place in Malang City that offers 2 main entertainment parks which contains lantern gardens and dinosaur parks. Malang Night Paradise provides service support through social networking and website usage. The background of the problem found is based on the results of the analysis of the initial data from researchers, stakeholders, and real users to produce findings that match the usability and interface problems. This analysis shows the symptoms of usability problems that need to be evaluated referring to 3 aspects, namely effectiveness, efficiency, and user satisfaction based on the quality of information and interface and consideration of the improvement of interface in the form of solution design. Overall, this research uses Human Centered Design (HCD) method. To support usability evaluation, a Post-Study System Usability Questionnaire (PSSUQ) questionnaire was used to measure usability aspects of user satisfaction and qualitative data requirements. The guidelines in the form of design reference used in this research is the Health and Human Services (HHS) guidelines. This research resulted an increase usability values from the initial design to the design of the solution so that the evaluation of usability can be declared successful. The average value of effectiveness obtained from the initial design was 42.85% then the design of the solution increased to 100%. The average efficiency value obtained from the initial design was 41.18%, then the design solution increased to 100%. The average value of user satisfaction from the initial design in the percentage obtained was 41.50%. Then in the design of the solution increased to 92.19%.